Elevated Levels of Circulating Procoagulant Microparticles in Patients With Paroxysmal Nocturnal Hemoglobinuria and Aplastic Anemia - Hugel, Bénédicte; Socié, Gérard; Vu, Thi; Toti, Florence; Gluckman, Eliane; Freyssinet, Jean-Marie; Scrobohaci, Marie-Lorraine (Blood, 1999)
Paroxysmal nocturnal hemoglobinuria (PNH), frequently occurring during suppressed hematopoiesis including aplastic anemia (AA), is a clonal disorder associated with an increased incidence of thrombotic events. Complement-mediated hemolysis, impairment of the fibrinolytic system, or platelet activation are thought to be responsible for the associated thrombotic risk. We investigated here the elevation of membrane-derived procoagulant microparticles in the blood flow of such patients. Elevated levels of circulating microparticles were in fact detected in both de novo PNH patients and AA subjects with a PNH clone, but not in those with AA without a PNH clone. The cellular origin of the microparticles was determined in PNH samples; most stemmed from platelets. Glycophorin A+ particles were rarely detected. Therefore, platelet activation, resulting in the dissemination of procoagulant phospholipids in the blood flow, could be one of the main causes for the elevated thrombotic risk associated with PNH. These observations suggest that shed membrane particles can be considered a valuable biological parameter for the assessment of possible thrombotic complications in patients with PNH.